Non-shunt Management of Communicating Hydrocephalus in an Immunocompetent Host With Disseminated Central Nervous System Coccidioidomycosis - Sanjay V. Menghani PhD; Chelsea L. Takamatsu MD; Ramzi Ibrahim MD; Lupita Molina BS; Neha Jaswal MD; Fariba M. Donovan MD, PhD (SAGE Publishing, 2023)
Disseminated coccidioidomycosis is associated with significant morbidity and mortality. Involvement of the meninges is often fatal if untreated, typically requiring lifelong antifungal therapy and neurosurgical intervention. We present the case of a young male without any known immunocompromising conditions who opted exclusively for medical management of newly diagnosed coccidioidomycosis meningitis with communicating hydrocephalus and discuss the controversy associated with this approach. This case highlights the importance of shared decision-making between patient and clinician, even if the plan diverges from available guidelines. Furthermore, we discuss clinical considerations in approaching the close outpatient monitoring of patients with central nervous system coccidioidomycosis with hydrocephalus.